2019
DOI: 10.1113/ep087599
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia speeds pulmonary oxygen uptake kinetics and increases critical power during supine cycling

Abstract: New Findings What is the central question of this study?Critical power is a fundamental parameter defining high‐intensity exercise tolerance and is related to the phase II time constant of pulmonary oxygen uptake kinetics (τtrueV̇O2). To test whether this relationship is causal, we assessed the impact of hyperoxia on τtrueV̇O2 and critical power during supine cycle exercise. What is the main finding and its importance?The results demonstrate that hyperoxia increased muscle oxygenation, reduced τtrueV̇O2 (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 49 publications
(112 reference statements)
1
36
0
Order By: Relevance
“…Furthermore, in a recent study we demonstrated that hyperoxia speeded pulmonary O 2 kinetics and increased CP during supine exercise, but that the change in ! O2 did not correlate linearly with the change in CP (9). Taken together, the relative, independent contributions of !…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Furthermore, in a recent study we demonstrated that hyperoxia speeded pulmonary O 2 kinetics and increased CP during supine exercise, but that the change in ! O2 did not correlate linearly with the change in CP (9). Taken together, the relative, independent contributions of !…”
Section: Introductionmentioning
confidence: 80%
“…[HbO + MbO 2 ] was increased during both moderate (hyperoxia: 74 ± 21 µM, normoxia: ± 18; main effect of condition, P < 0.001, Figure 4A) and severe (hyperoxia: 73 ± 20 µM, normoxia: 66 ± 15; main effect of condition, P = 0.039, Figure 4B) Figure 3A) or severe exercise ( Figure 3B, kinetics increases CP (7,9), and also that a slowing of the O 2 kinetics decreases CP (6,8).…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations